Population carrier rates of pathogenic ARSA gene mutations: is metachromatic leukodystrophy underdiagnosed? - Agnieszka Ługowska; Joanna Ponińska; Paweł Krajewski; Grażyna Broda; Rafał Płoski (PLoS ONE, 2011)
BACKGROUND: Metachromatic leukodystrophy (MLD) is a severe neurometabolic disease caused mainly by deficiency of arylsulfatase A encoded by the ARSA gene. Based on epidemiological surveys the incidence of MLD per 100,000 live births varied from 0.6 to 2.5. Our purpose was to estimate the birth prevalence of MLD in Poland by determining population frequency of the common pathogenic ARSA gene mutations and to compare this estimate with epidemiological data. METHODOLOGY: We studied two independently ascertained cohorts from the Polish background population (N∼3000 each) and determined carrier rates of common ARSA gene mutations: c.459+1G>A, p.P426L, p.I179S (cohort 1) and c.459+1G>A, p.I179S (cohort 2). PRINCIPAL FINDINGS: Taking into account ARSA gene mutation distribution among 60 Polish patients, the expected MLD birth prevalence in the general population (assuming no selection against homozygous fetuses) was estimated as 4.0/100,000 and 4.1/100,000, respectively for the 1(st) and the 2(nd) cohort with a pooled estimate of 4.1/100,000 (CI: 1.8-9.4) which was higher than the estimate of 0.38 per 100,000 live births based on diagnosed cases. The p.I179S mutation was relatively more prevalent among controls than patients (OR = 3.6, P = 0.0082, for a comparison of p.I179S frequency relative to c.459+1G>A between controls vs. patients). CONCLUSIONS/SIGNIFICANCE: The observed discrepancy between the measured incidence of metachromatic leukodystrophy and the predicted carriage rates suggests that MLD is substantially underdiagnosed in the Polish population. The underdiagnosis rate may be particularly high among patients with p.I179S mutation whose disease is characterized mainly by psychotic symptoms.